PENGARUH FASILITAS RUMAH TERHADAP KESEJAHTERAAN MASYARAKAT KABUPATEN KEPULAUAN MENTAWAI - Illahi, Feby Mega; Ariusni, Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study aims to determine: (1) The Effect of Electricity Availability on people's welfare. (2) Effect of Availability of Clean Water on people’s welfare. (3) Effect of Sanitation on people's welfare. (4) Effect of Housing Ownership Status on people's welfare. (5) Effects of Electricity Availability, Availability of Clean Water, Sanitation and Home Ownership Status on people's welfare. This type of research is descriptive and associative. The type of data used is secondary data, namely 2018 SUSENAS data conducted by the Central Statistics Agency (BPS). The analytical tool used is multiple linear regression analysis.The results of this study indicate that: (1) Electricity Availability has a positive and significant effect on people's welfare. (2) The availability of clean water has a positive and significant effect on people's welfare. (3) Sanitation has a positive and significant effect on people's welfare. (4) House Ownership Status has a negative and not significant effect on people's welfare. (5) Availability of Electricity, Availability of Clean Water, Sanitation and Home Ownership Status has a positive and significant impact on people's welfare.Based on the results of the study, it is recommended that the Mentawai Islands Regency government focus on infrastructure development especially those related to electricity, clean water and sanitation. This is done so that the welfare of the people in the Mentawai Islands Regency can be improved.